Beyond structure: integration of organization theory and organizational design for strategic flexibility - Onyshchenko, Oksana (Management and Entrepreneurship: Trends of Development, 2025)
In today's turbulent and digital transformation environment, traditional approaches to organizational design that focus on formal structures are increasingly proving insufficient to ensure strategic flexibility of enterprises. At the same time, the provisions of Organization Theory offer a deeper explanation of behavioral and institutional mechanisms, but remain fragmentarily integrated into management practice. The article attempts to synthesize these two planes – scientific and applied – by developing a conceptual framework “beyond structure”, which goes beyond the traditional idea of the organizational chart as the main adaptation tool.The authors focus on the key contradictions of modern organizational design: finding a balance between stability and adaptability, form and mechanisms, static “fit” and dynamic “fitness”. The vision of strategic flexibility is proposed as the ability of an organization to quickly reallocate resources, reduce the decision-making cycle, scale innovations and maintain manageability in the process of change. The article identifies micromechanisms that mediate this process: role design, coordination protocols, information flow architecture, decision-making rights distribution, and digital infrastructure.The practical value of the study lies in the formation of a toolkit for managers that allows them to diagnose “rigidity nodes,” apply design principles to increase flexibility without radical restructuring, and integrate scientific insights from Organization Theory into specific management practices. The theoretical significance lies in the development of an interdisciplinary approach to organizational design that takes into account the dynamics of the environment, microfoundations of adaptation, and digital architecture as a basic element of modern organizational systems.JEL Classification: L2, L21, L22, M1, M10